SOME FACTORS RELATED TO KNOWLEDGE AND PRACTICE OF USING ANTIBIOTIC DRUGS FOR CHILDREN UNDER 5 YEARS OLD CHILDREN IN TWO COMMUNITIES, KIEN XUONG DISTRICT, THAI BINH PROVINCE, 2020 (Vietnam Journal of Community Medicine, 2021)
Objective: To identify some related factors of caregiver use of antibiotics in under 5 years old in twocommunes, Kien Xuong district, Thai Binh province by 2020.Study object: caregivers in two communes of Kien Xuong district, Thai BinhResearch method: Epidemiological method described through cross-sectional investigation withanalysis.Research results: There is a relationship between educational attainment, number of children,economic conditions and age with knowledge of antibiotic use: the proportion of subjects withhigh school knowledge has achieved Antibiotic use is 1.8 times more likely than the group witheducation from high school or less, 95% CI (1.1-2.9). Regarding practice, there is a relationshipbetween knowledge, age of research subjects, parents of children and practice of using antibiotics.the rate of subjects with knowledge achieved with practice is 3.9 times higher than the group withsuccessful practice with unsatisfactory knowledge; The percentage of study subjects who are parentsof children having practice of antibiotic drugs is likely to be 2.5 times higher than that of the child’sgrandparents.
Keywords: Antibiotics, children under 5 years old, related factors